Washed microbiota transplantation: a case report of clinical success with skin and gut microbiota improvement in an adolescent boy with atopic dermatitis - Deng, Wan-Ying; Chen, Wen-Jia; Zhong, Hao-Jie; Wu, Li-Hao; He, Xing-Xiang (Frontiers in Immunology, 2023)
Atopic dermatitis (AD) is a chronic, recurrent inflammatory disease characterized by itching. The gut microbiome can help maintain skin immune homeostasis by regulating innate and adaptive immunity. Here, we report a case of AD in a 15-year-old adolescent boy who benefited from washed microbiota transplantation (WMT). WMT was performed for three courses, with each course lasting for three consecutive days and an interval of one month between two courses. Clinical assessments were conducted at each WMT course, and skin, blood, and stool samples were collected for microbial analysis. After three months of WMT treatment, the boy's itchiness was effectively controlled: his skin showed noticeable improvement, with reduced Staphylococcus aureus in the skin lesions. The scores of SCORAD (SCORing Atopic Dermatitis), EASI (Eczema Area and Severity Index), NRS (Numerical Rating Scale), and DLQI (Dermatology Life Quality Index) significantly decreased compared to the baseline. Serum levels of eosinophil ratio, tumor necrotic factor-α, and interleukin-6 also reduced to the normal levels. There was a significant decrease in S. aureus in the skin lesions. Additionally, the intestinal flora became more diverse, and the abundance of Bifidobacterium species, significantly increased after WMT. No adverse events were reported during the treatment and the 1-year follow-up period. This case report provides direct clinical evidence for WMT as a novel promising treatment strategy for AD, and preliminary experimental data suggests the existence of an intestinal-skin axis in terms of the gut microbiota and the 3 skin immune homeostasis.